2020
DOI: 10.1097/md.0000000000022744
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic cervical foraminotomy as a new treatment for cervical radiculopathy

Abstract: Background: Anterior cervical discectomy and fusion (ACDF) is the gold standard treatment for this cervical radiculopathy. Posterior endoscopic cervical foraminotomy (PECF), an effective alternative to ACDF, is becoming widely used by an increasing number of surgeons. However, comparisons of the clinical outcomes of ACDF and PECF remain poorly explored. The purpose of this study was to evaluate and compare visual analog scale (VAS)-arm scores, VAS-neck scores, neck disability index (NDI) scores, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
19
2
Order By: Relevance
“…As previous literature reports about the lumbar synovial cysts removal, the posterior endoscopic approach reduces the muscle denervation and decreases the risk of postoperative hematoma. It preserves the range of segmental motion and shortens the patient's recovery time [ 26 , 27 ]. We hope to transfer the above technical superiority to cervical spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As previous literature reports about the lumbar synovial cysts removal, the posterior endoscopic approach reduces the muscle denervation and decreases the risk of postoperative hematoma. It preserves the range of segmental motion and shortens the patient's recovery time [ 26 , 27 ]. We hope to transfer the above technical superiority to cervical spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al .from the First Affiliated Hospital of University of South China, conducted a systematic review and meta-analysis of the studies done for percutaneous endoscopic cervical foraminotomy (PECF or FECF). 30 This was the only meta-analysis done specifically for endoscopic PCF and did not include other minimally invasive PCF approaches. It was interesting to note that in addition to indicating that VAS-arm scores were much better for PECF approach, the VAS-arm and NDI scores also showed a favorable trend over a median period of follow up of 20.9 months.…”
Section: What Are the Advantages Of Posterior Approach And What Have Been The Arguments Against It?mentioning
confidence: 99%
“…It avoids excessive stripping of the posterior cervical muscle groups, reducing intraoperative bleeding, soft tissue injury and postoperative axial pain 19 . Several studies have demonstrated that full endoscopic cervical spine surgery is a safe, effective and promising alternative to conventional procedures on properly selected patients 20–22 …”
Section: Introductionmentioning
confidence: 99%
“…19 Several studies have demonstrated that full endoscopic cervical spine surgery is a safe, effective and promising alternative to conventional procedures on properly selected patients. [20][21][22] The "key-hole" technique is the basis of minimally invasive full endoscopic posterior cervical foraminotomy and discectomy (FPCD). And accurate localization of the "V" point (the intersection of the upper and lower lamina with the articular process)is a crucial step of the "key-hole" technique.…”
Section: Introductionmentioning
confidence: 99%